How Can Social Psychology and Group Dynamics Assist in Curriculum Development?. (April 2014) - Chin, Jeffrey; May, Matthew; Sullivan-Chin, Honora; Woodrick, Kaylyn
This article discusses some of the challenges departments face as they embark on curriculum development. The interpersonal dynamics of a department are often the first and most difficult obstacle to overcome but are often overlooked. The author suggests some strategies for how to address these issues as they arise.